Characterisation of Phytophthora inundata according to host range, morphological variation and multigene molecular phylogeny - SAFAIEFARAHANI, Banafsheh; MOSTOWFIZADEH-GHALAMFARSA, Reza; COOKE, David (Phytopathologia Mediterranea, 2012)
Phytophthora inundata is an Oomycetous plant pathogen that has been isolated from a range of different plant species. Although formally described in 2003, relatively little further characterisation of this taxon has been reported. This study presents an approach to phylogenetic discrimination of P. inundata based on concordance of multiple gene genealogies in relation to the host range and morphological traits of isolates from Iran (Beta vulgaris, Pistacia vera, Solanum nigrum and river water), United Kingdom (Salix matsudana), Spain (Olea sp.) and the United States of America (unknown host). Isolates were identified by rDNA internal transcribed spacer (ITS) sequence analysis, followed by assessment of pathogenicity, morphological, physiological (cultural, temperature relations and mating) and molecular traits. Multiple gene genealogy analyses were performed on regions of nuclear (ITS, β-tubulin, translation elongation factor 1α) and mitochondrial (cytochrome c oxidase subunit I) gene sequences of this and other major Phytophthora species. Congruence was observed in different phylogenetic data sets. Maximum likelihood phylogenetic reconstruction based on the different genes indicated that, although there is some variation between morphological and mating behaviour of P. inundata isolates, this taxon is a distinct and homogeneous species which always appeared as a sister taxon to P. humicola. Phytophthora inundata is shown to be a uniform species, with isolates from wide-ranging geographic origins having similar host ranges, molecular, and morphological characteristics.